FUN PIANO LESSON FOR YOUNG BEGINNERS STUDENTS IN SURABAYA INDONESIA - Yulisetiana, FNU (Sanata Dharma University Yogyakarta, 2019)
Learning piano is not an easy thing, moreover for young beginner learners. The teacher of course not only giving materials to students but also considering the approach given to the young beginner students. The teacher is also needed to be creative, and always developing the ability in techniques and approach to children. This study tried to discuss how to make piano lessons fun. This research method uses grounded research with a focus on theoretical studies on piano learning through the views of piano experts, including Dalcroze, Suzuki, Schulwerk, and Kodaly. After that, the data is analyzed using content analysis. The results of the study showed that by exploring the viewpoint of Dalcroze, Suzuki, Schulwerk, and Kodaly piano learning, art learning must be set pleasantly by the teacher. The role of the teacher and student must also have a good relationship because, in pleasant learning, an effective correlation between learning materials, teachers, and students is needed.DOI: doi.org/10.24071/ijiet.2019.030204